2023
DOI: 10.3390/plants12112190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Calcium Silicate in Enhancing Soybean Growth and Yield

John Quarshie Attipoe,
Waleed Khan,
Rupesh Tayade
et al.

Abstract: The application of silicon (Si) fertilizer positively impacts crop health, yield, and seed quality worldwide. Si is a “quasi-essential” element that is crucial for plant nutrition and stress response but is less associated with growth. This study aimed to investigate the effect of Si on the yield of cultivated soybean (Glycine max L). Two locations, Gyeongsan and Gunwi, in the Republic of Korea were selected, and a land suitability analysis was performed using QGIS version 3.28.1. The experiments at both locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 84 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…TRL demonstrated a negative association with AD while, conversely, positive associations with RV, NT, NF, and TTL (Figure 3). This pattern of association can be attributed to the inverse relationship between root length and thickness, as reported in previous studies [35,36]. Furthermore, thinner roots typically exhibit a higher fibrous nature and a greater propensity for branching than thicker roots [37,38].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…TRL demonstrated a negative association with AD while, conversely, positive associations with RV, NT, NF, and TTL (Figure 3). This pattern of association can be attributed to the inverse relationship between root length and thickness, as reported in previous studies [35,36]. Furthermore, thinner roots typically exhibit a higher fibrous nature and a greater propensity for branching than thicker roots [37,38].…”
Section: Discussionsupporting
confidence: 70%
“…A longer TRL and other improved RMTs serve as positive indicators for a plant's tolerance to abiotic stresses, overall crop growth, and yield output [36]. Improved RMTs enable plants to cover more soil layers and access more nutrient hotspots and water profiles [37,40,41,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that bigger seeds didn’t make the yield better; in fact, they sometimes made the yield lower compared to smaller seeds, especially in good growing conditions. Similarly, another study reported a negative correlation of HSW ( r = -0.05) with yield while a significant positive correlation of pod number ( r = 0.44), and total grain number ( r = 0.44) was noticed with the yield output ( Attipoe et al., 2023 ) while contrastingly, some studies have revealed different results. A study conducted to check the effect of SS on crop yield, including others, has revealed a positive impact, where larger seeds produced an increase of 5.4% on average from the small seeds genotypes in 10 experiments ( Smith and Camper, 1975 ), furthermore, a separated study also revealed high crop yield for the accessions having larger SS comparatively to the smaller genotypes ( Adebisi et al., 2013 ), adding more, another study conducted revealed NPP, total number of seeds, and HSW showed a positive correlation of ( r = 0.92), ( r = 0.93), and ( r = 0.063) with yield, respectively ( Vu et al., 2019 ).…”
Section: Key Seed Yield Traits and Significance For Crop Improvementmentioning
confidence: 90%
“…A study conducted to check the effect of SS on crop yield, including others, has revealed a positive impact, where larger seeds produced an increase of 5.4% on average from the small seeds genotypes in 10 experiments ( Smith and Camper, 1975 ), furthermore, a separated study also revealed high crop yield for the accessions having larger SS comparatively to the smaller genotypes ( Adebisi et al., 2013 ), adding more, another study conducted revealed NPP, total number of seeds, and HSW showed a positive correlation of ( r = 0.92), ( r = 0.93), and ( r = 0.063) with yield, respectively ( Vu et al., 2019 ). Analyzing the mentioned studies, it can be concluded that the most important and defining traits contributing to crop yield directly are the pods number and number of seeds, revealing the biggest correlation with the yield in every study conducted ( Adebisi et al., 2013 ; Attipoe et al., 2023 ). However, relying solely on simple correlation to establish the causal relationship between yield components and yield might not accurately capture the intricate cause-and-effect dynamics, thus leading to potential inefficiencies in the selection strategy.…”
Section: Key Seed Yield Traits and Significance For Crop Improvementmentioning
confidence: 99%
“…Apart from seed size, seed number is another important agronomic parameter used for estimating the grain weight and yield and has an essential role in soybean breeding [8]. The total number of seeds per plant, total seeds per selected area, and seeds per pod are the main traits used for estimating the yield of soybean [9].…”
Section: Introductionmentioning
confidence: 99%